Investing for Impact : The Global Impact Investing Market 2020 - International Finance Corporation (International Finance Corporation, Washington, DC, 2021)
Impact investing has seen a boost in popularity during the COVID-19 (coronavirus) pandemic due to increased awareness of climate change and social challenges such as unequal access to healthcare and racial and gender inequality. In 2020, the market saw an increasing level of maturity compared to 2019 with more assets being invested with identifiable impact management systems. This report covers impact investments by privately owned funds and institutions, and by publicly owned development finance institutions and development banks. It includes all investments with an intent for impact and identifies a core which have impact management systems to provide a credible contribution to impact and measurement of impact. Intent, contribution and measurement are the key attributes which differentiate impact investing from other forms of sustainable or responsible investing. In total, the report identifies a total of 2.3 trillion Dollars being invested for impact in 2020. This is equivalent to about 2 percent of global AUM. Impact investing remains a small market niche, but one that is attracting growing interest. Additionally, the report shares findings on broader trends relating to investing for impact, including opportunities in publicly traded assets. IFC's report is the most comprehensive assessment so far of the size of the global impact investing market. Findings from the report are based on publicly available information and verifiable data from selected proprietary databases.